Modelling the probability of youth unemployment in Australia - Harris, Mark (ECONOMIC SOC OF AUSTRALIA BROWN PRIOR ANDERSON PTY LTD, 1996)
This paper attempts to explain how particular personal characteristics affect the probability of Australian youth unemployment. Results indicate that generally age, education and financial commitments exert a positive influence on employment prospects. Also, there is evidence to suggest that the disabled are disadvantaged in the workplace and that women are less likely to supply their labour if they have children. The results are compared to the known effects of personal characteristics on the duration of unemployment, pointing policy clearly in the direction of age, education and reservation wages.